Urea formaldehyde production process
By controlling the mass ratio of water, urea and formaldehyde to generate urea formaldehyde with a higher cross-linking degree, and adding modified adsorbents and formaldehyde degrading bacteria to it, the problem of formaldehyde contamination in production and application is solved, and a lower level of urea formaldehyde has been achieved. environmental pollution and higher nitrogen fertilizer effects.
Patent Information
- Application Number
- CN202411437906.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The formaldehyde produced by urea formaldehyde during production and application has an adverse impact on the environment, and its decomposition cycle is long, resulting in environmental pollution.
The reaction is carried out by controlling the mass ratio of water, urea and formaldehyde to generate urea formaldehyde with crosslinking degree, and a modified adsorbent is added to the post-treatment, especially chitosan-nano-crystalline cellulose composite aerogel and burying Sodium alginate gel powder with formaldehyde degradation bacteria is used to absorb and fix free formaldehyde and reduce its volatility and diffusion.
It effectively reduces the generation and decomposition of formaldehyde in the production process of urea formaldehyde, reduces the formaldehyde content during use, reduces the pollution to the environment, and improves the reaction completeness of urea formaldehyde and the effect of nitrogen fertilizer, and promotes plant growth.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of urea formaldehyde, and more specifically, to a urea formaldehyde production process. Background Art
[0002] Urea formaldehyde is a polymer obtained by the reaction of urea and formaldehyde, also known as urea-formaldehyde resin or urea-formaldehyde resin. It is a thermosetting resin with good water resistance, aging resistance, chemical corrosion resistance and insulation properties, so it is widely used in various fields, such as the manufacture of adhesives, coatings, molding compounds, etc. At the same time, urea formaldehyde can be used as a fertilizer, and the urea produced by the decomposition of urea formaldehyde can be used as a nitrogen source to provide nitrogen sources for soil and crops. The decomposition rate of urea formaldehyde is relatively slow, and it can be used as a slow-release fertilizer to provide a continuous and long-term nitrogen source.
[0003] Urea formaldehyde has poor thermal stability and is easily decomposed to produce formaldehyde and urea. Free formaldehyde can be absorbed and degraded by microorganisms or plants in the environment, but the decomposition of formaldehyde requires a certain period of time. The decomposition period of urea formaldehyde is relatively long, and free formaldehyde and formaldehyde produced by decomposition will appear. Before formaldehyde is absorbed and degraded, it will still have an adverse effect on the environment. Summary of the invention
[0004] In order to reduce the formaldehyde generated during the production and application of urea formaldehyde, the present application provides a urea formaldehyde production process, which adopts the following technical solution: A urea formaldehyde production process comprises the following steps: Preheating: After the reactor is heated to 45-55°C, hot water at 45-55°C is introduced; Dissolution: Continue steam heating, raise the temperature of the reactor to 70-80°C, add urea while stirring, and continue steam heating to 90-100°C; Urea-formaldehyde reaction: add 35-38 wt% formaldehyde solution into the reactor, stop steam heating, and continue stirring and reacting for 15-20 minutes to obtain urea-formaldehyde; Post-treatment: After the urea formaldehyde is cooled to 20-25°C, the modified adsorbent is added to the urea formaldehyde and mixed evenly to obtain the urea formaldehyde finished product.
[0005] By adopting the above technical scheme, at high temperature, the solubility of urea in water increases, urea reacts with formaldehyde to generate monomethylol urea and dimethylol urea, and adjacent methylol urea molecules are connected by methylene bonds or dimethylene ether bonds to form a polymer, and finally a polymer with a certain degree of cross-linking, i.e., urea formaldehyde, is formed. By controlling the temperature and the amount of raw material added during the production process, the formaldehyde generated during the production process of urea formaldehyde is reduced. In the post-treatment, a modified adsorbent is added to the urea formaldehyde. The modified adsorbent has good adsorption properties, can absorb the formaldehyde and free formaldehyde generated by the decomposition of urea formaldehyde, enrich the free formaldehyde, reduce the volatilization and diffusion of formaldehyde, and reduce the formaldehyde generated when urea formaldehyde is used.
[0006] Preferably, the mass ratio of water, urea and formaldehyde solution is (0.43-0.45):(3.98-4.01):(1.01-1.07).
[0007] By adopting the above technical scheme, the mass ratio of water, urea and formaldehyde is controlled, thereby controlling the rate and process of the reaction of urea and formaldehyde, improving the completeness of the reaction of urea and formaldehyde, reducing the generation of free formaldehyde, and reducing the decomposition of urea formaldehyde.
[0008] Preferably, the modified adsorbent is added in an amount of 0.2-0.3 g / L in the urea formaldehyde finished product.
[0009] By adopting the above technical scheme, the amount of modified adsorbent added to urea formaldehyde is controlled so that the modified adsorbent can fully adsorb free formaldehyde and at the same time the modified adsorbent can be evenly dispersed in the urea formaldehyde product, thereby reducing the impact of the modified adsorbent on the performance of urea formaldehyde.
[0010] Preferably, the modified adsorbent is chitosan-nanocrystalline cellulose composite aerogel.
[0011] By adopting the above technical scheme, chitosan and nanocrystalline cellulose have a large specific surface area, so that the chitosan-nanocrystalline cellulose composite aerogel can fix formaldehyde by physical adsorption. At the same time, chitosan contains more amino groups, which can combine with the aldehyde group of formaldehyde to fix formaldehyde by chemical bonding. Nanocrystalline cellulose contains a large number of hydroxyl groups, which can form a chemical covalent bond with formaldehyde, thereby fixing the formaldehyde.
[0012] Preferably, the preparation method of the chitosan-nanocrystalline cellulose composite aerogel comprises the following steps: dispersing nanocrystalline cellulose in a 2-3wt% acetic acid solution, adding chitosan, stirring until completely dissolved to obtain a mixed solution, adding potassium persulfate, reacting for 10-12 minutes, adding acrylic acid solution and sodium hydroxide solution, and then adding acrylamide, ultrasonically dispersing until uniformly dispersed, adding N,N'-methylenebisacrylamide solution, reacting for 30-40 minutes, continuing to react at 60°C for 6 hours, dialyzing for 7 days, and freeze-drying to obtain the chitosan-nanocrystalline cellulose composite aerogel.
[0013] By adopting the above technical scheme, nanocrystalline cellulose aerogel is used as a matrix and compounded with chitosan to prepare chitosan-nanocrystalline cellulose composite aerogel. Both chitosan and nanocrystalline cellulose contain a large number of amino groups and hydroxyl groups, which can combine with the aldehyde group of formaldehyde to adsorb and fix formaldehyde, thereby completing the enrichment of formaldehyde.
[0014] Preferably, the chitosan-nanocrystalline cellulose composite aerogel is further post-treated as follows: epichlorohydrin, perchloric acid solution and anhydrous ethanol are mixed to obtain a mixed solution, the chitosan-nanocrystalline cellulose composite aerogel is placed in the mixed solution, allowed to stand for 12 hours, washed with anhydrous ethanol, heated in a water bath at 50° C. and a mixed solution of ethylenediamine and anhydrous ethanol is added, allowed to stand for 12 hours, and freeze-dried.
[0015] By adopting the above technical scheme, after the chitosan-nanocrystalline cellulose composite aerogel is treated with a mixed solution, ethylenediamine is added to complete the amination process of the chitosan-nanocrystalline cellulose composite aerogel, so that the chitosan-nanocrystalline cellulose composite aerogel contains a large amount of amino groups, thereby improving the adsorption performance of the chitosan-nanocrystalline cellulose composite aerogel for formaldehyde.
[0016] Preferably, in the post-treatment, before adding the modified adsorbent, the following treatment is performed: ultrasonically dispersing the modified adsorbent in water, adding sodium alginate gel powder embedding formaldehyde-degrading bacteria, ultrasonicating for 20-25 minutes, standing for 30-35 minutes, and freeze-drying.
[0017] By adopting the above technical scheme, formaldehyde-degrading bacteria are embedded in sodium alginate gel powder, the gel powder is evenly dispersed by ultrasonication, evenly mixed with chitosan-nanocrystalline cellulose composite aerogel and adsorbed and fixed in the chitosan-nanocrystalline cellulose composite aerogel, and the chitosan-nanocrystalline cellulose composite aerogel adsorbs and fixes free formaldehyde in urea formaldehyde, thereby completing the enrichment of free formaldehyde, and the formaldehyde-degrading bacteria can decompose the enriched formaldehyde, thereby reducing the content and diffusion of free formaldehyde.
[0018] Preferably, the mass ratio of the chitosan-nanocrystalline cellulose composite aerogel to the sodium alginate gel powder embedded with formaldehyde-degrading bacteria is 1:(0.08-0.12).
[0019] By adopting the above technical solution, the amount of sodium alginate gel powder embedded with formaldehyde-degrading bacteria is controlled, so that the formaldehyde-degrading bacteria can effectively decompose formaldehyde, and at the same time, the sodium alginate gel powder can be evenly distributed and is not easy to agglomerate.
[0020] Preferably, the preparation method of the sodium alginate gel powder embedded with formaldehyde-degrading bacteria is as follows: formaldehyde-degrading bacteria are dispersed in physiological saline to obtain a bacterial suspension, the bacterial suspension is mixed with a sodium alginate solution and stirred evenly, a 4wt% calcium chloride solution is added dropwise, and the sodium alginate microspheres are placed in physiological saline for 2-2.5 hours to form, and the sodium alginate microspheres are placed in physiological saline for 12-13 hours of curing at 4-6°C, and then centrifuged and dried to obtain the sodium alginate gel powder embedded with formaldehyde-degrading bacteria.
[0021] By adopting the above technical scheme, formaldehyde-degrading bacteria are dispersed in physiological saline and mixed with sodium alginate. By adding calcium chloride, the sodium alginate is cross-linked to form gel microspheres. At the same time, the formaldehyde-degrading bacteria in the bacterial suspension are embedded, making it difficult for the formaldehyde-degrading bacteria to leak and be easily affected by the external environment. The survival rate of the formaldehyde-degrading bacteria is effectively improved, so that the formaldehyde-degrading bacteria can play its role in decomposing formaldehyde.
[0022] In summary, this application has the following beneficial effects: 1. In the present application, the mass ratio of water, urea and formaldehyde is controlled, thereby controlling the rate and process of the reaction of urea and formaldehyde, improving the completeness of the reaction of urea and formaldehyde, reducing the generation of free formaldehyde, and reducing the decomposition of urea formaldehyde.
[0023] 2. A modified adsorbent is added to the present application. The modified adsorbent has good adsorption performance, can absorb formaldehyde and free formaldehyde produced by the decomposition of urea formaldehyde, enrich free formaldehyde, reduce the volatilization and diffusion of formaldehyde, and reduce the formaldehyde produced when urea formaldehyde is used.
[0024] 3. The modified adsorbent in the present application is chitosan-nanocrystalline cellulose composite aerogel. Chitosan and nanocrystalline cellulose have a large specific surface area, so that the chitosan-nanocrystalline cellulose composite aerogel can fix formaldehyde by physical adsorption. At the same time, chitosan contains more amino groups, which can combine with the aldehyde group of formaldehyde and fix formaldehyde by chemical bonding. Nanocrystalline cellulose contains a large number of hydroxyl groups, which can form a chemical covalent bond with formaldehyde, thereby fixing the formaldehyde. DETAILED DESCRIPTION
[0025] The present application is further described in detail below in conjunction with embodiments. Sodium alginate gel powder embedded with formaldehyde-degrading bacteria 1-2 Preparation Example 1
[0026] The formaldehyde-degrading bacteria are selected from existing formaldehyde-degrading strains with the function of degrading formaldehyde. In this preparation example, Bacillus subtilis P601 is selected and is deposited in the General Microbiological Center of China Microorganism Culture Collection Administration (CGMCC); the deposit number is: CGMCC NO.18343.
[0027] Formaldehyde-degrading bacteria were dispersed in physiological saline to prepare 2×10 8 / mL bacterial suspension, the bacterial suspension and 4wt% sodium alginate solution are mixed in a volume ratio of 1:1 and stirred evenly, and then 4wt% calcium chloride solution is dropped into it. After curing for 2 hours to form, the sodium alginate microspheres are placed in physiological saline, cured at 4°C for 13 hours, centrifuged and dried to obtain sodium alginate gel powder encapsulating formaldehyde-degrading bacteria.
[0028] Preparation Example 2 The formaldehyde-degrading bacteria are selected from existing formaldehyde-degrading strains with the function of degrading formaldehyde. In this preparation example, Bacillus subtilis P601 is selected and is deposited in the General Microbiological Center of China Microorganism Culture Collection Administration (CGMCC); the deposit number is: CGMCC NO.18343.
[0029] Formaldehyde-degrading bacteria were dispersed in physiological saline to prepare 2×10 8 / mL bacterial suspension, the bacterial suspension and 4wt% sodium alginate solution are mixed in a volume ratio of 1:1 and stirred evenly, and then 4wt% calcium chloride solution is dropped into it. After curing for 2.5h to form, the sodium alginate microspheres are placed in physiological saline, cured at 6°C for 12h, centrifuged and dried to obtain sodium alginate gel powder encapsulating formaldehyde-degrading bacteria. Chitosan-nanocrystalline cellulose composite aerogel 3-12
[0030] Preparation Example 3 Nanocrystalline cellulose was dispersed in 140 mL of 3 wt % acetic acid solution with a concentration of 0.017 wt %. 2.5 g of chitosan was added and stirred until completely dissolved to obtain a mixed solution. 3.4 g of potassium persulfate was added and reacted for 10 min. Then, 15 mL of 50 wt % acrylic acid solution and 8 mL of 40 wt % sodium hydroxide solution were added. Then, 0.9 g of acrylamide was added and ultrasonicated until uniformly dispersed. Then, 40 mL of 1.2 wt % N, N'-methylenebisacrylamide solution was added and reacted for 40 min. The reaction was continued at 60 ° C for 6 h, dialyzed for 7 days, and freeze-dried to obtain chitosan-nanocrystalline cellulose composite aerogel.
[0031] Preparation Example 4 Nanocrystalline cellulose was dispersed in 140 mL of 2 wt % acetic acid solution with a concentration of 0.014 wt %. 2 g of chitosan was added and stirred until completely dissolved to obtain a mixed solution. 3 g of potassium persulfate was added and reacted for 12 min. Then, 15 mL of 45 wt % acrylic acid solution and 8 mL of 35 wt % sodium hydroxide solution were added. Then, 0.7 g of acrylamide was added and ultrasonicated until uniformly dispersed. Then, 40 mL of 1 wt % N, N'-methylenebisacrylamide solution was added and reacted for 30 min. The reaction was continued at 60 ° C for 6 h, dialyzed for 7 days, and freeze-dried to obtain chitosan-nanocrystalline cellulose composite aerogel.
[0032] Preparation Example 5 The difference between Preparation Example 5 and Preparation Example 3 is that in Preparation Example 5, 0.1 g of chitosan is added.
[0033] Preparation Example 6 The difference between Preparation Example 6 and Preparation Example 3 is that in Preparation Example 6, 5 g of chitosan is added.
[0034] Preparation Example 7 The difference between Preparation Example 7 and Preparation Example 3 is that in Preparation Example 7, the chitosan-nanocrystalline cellulose composite aerogel is also subjected to the following post-treatment: 18 mL of epichlorohydrin, 10 mL of 70 wt% perchloric acid solution, and 260 mL of anhydrous ethanol are mixed to prepare a mixed solution, the chitosan-nanocrystalline cellulose composite aerogel is placed in the mixed solution, allowed to stand for 12 h, washed with anhydrous ethanol, heated in a water bath at 50°C and a mixed solution of 15 mL of ethylenediamine and 50 mL of anhydrous ethanol is added, allowed to stand for 12 h, and freeze-dried.
[0035] Preparation Example 8 The difference between Preparation Example 8 and Preparation Example 3 is that in Preparation Example 8, the chitosan-nanocrystalline cellulose composite aerogel is also subjected to the following post-treatment: 14 mL of epichlorohydrin, 8 mL of 70 wt% perchloric acid solution, and 250 mL of anhydrous ethanol are mixed to prepare a mixed solution, the chitosan-nanocrystalline cellulose composite aerogel is placed in the mixed solution, allowed to stand for 13 h, washed with anhydrous ethanol, heated in a water bath at 50°C and a mixed solution of 18 mL of ethylenediamine and 50 mL of anhydrous ethanol is added, allowed to stand for 12 h, and freeze-dried.
[0036] Preparation Example 9 The difference between Preparation Example 9 and Preparation Example 7 is that in Preparation Example 9, the modified adsorbent is subjected to the following treatment: after the modified adsorbent is ground and crushed, it is ultrasonically dispersed in water, and sodium alginate gel powder embedded with formaldehyde-degrading bacteria is added, the mass ratio of chitosan-nanocrystalline cellulose composite aerogel to sodium alginate gel powder embedded with formaldehyde-degrading bacteria is 1:0.08, after ultrasonication for 20-25 minutes, it is allowed to stand for 30-35 minutes and freeze-dried.
[0037] Preparation Example 10 The difference between Preparation Example 10 and Preparation Example 7 is that in Preparation Example 10, the modified adsorbent is subjected to the following treatment: after the modified adsorbent is ground and crushed, it is ultrasonically dispersed in water, and sodium alginate gel powder embedded with formaldehyde-degrading bacteria is added, the mass ratio of chitosan-nanocrystalline cellulose composite aerogel to sodium alginate gel powder embedded with formaldehyde-degrading bacteria is 1:0.12, and after ultrasonication for 20-25 minutes, it is allowed to stand for 30-35 minutes and freeze-dried.
[0038] Preparation Example 11 The difference between Preparation Example 11 and Preparation Example 9 is that in Preparation Example 9, the mass ratio of chitosan-nanocrystalline cellulose composite aerogel to sodium alginate gel powder embedded with formaldehyde-degrading bacteria is 1:0.02.
[0039] Preparation Example 12 The difference between Preparation Example 12 and Preparation Example 9 is that in Preparation Example 12, the mass ratio of chitosan-nanocrystalline cellulose composite aerogel to sodium alginate gel powder embedded with formaldehyde-degrading bacteria is 1:0.18. Example
[0040] Example 1 A urea formaldehyde production process, characterized in that it comprises the following steps: Preheating: After the reactor is heated to 45°C, 430kg of 45°C hot water is introduced; Dissolution: Continue steam heating, raise the temperature of the reactor to 70°C, add 3980kg urea while stirring, and continue steam heating to 90°C; Urea-formaldehyde reaction: add 101kg 35wt% formaldehyde solution into the reactor, and stop steam heating at the same time. After the addition of formaldehyde solution, the temperature in the reactor is 90°C, and the reaction is continued with stirring for 15 minutes to obtain urea-formaldehyde; Post-treatment: After the urea formaldehyde is cooled to 20°C, a modified adsorbent is added to the urea formaldehyde and mixed evenly. The amount of the modified adsorbent added to the urea formaldehyde product is 0.2 g / L to obtain a urea formaldehyde product. The modified adsorbent is the chitosan-nanocrystalline cellulose composite aerogel obtained in Preparation Example 3.
[0041] Example 2 A urea formaldehyde production process, characterized in that it comprises the following steps: Preheating: After the reactor is heated to 55°C, 450kg of 55°C hot water is introduced; Dissolution: Continue steam heating, raise the temperature of the reactor to 80°C, add 4010kg urea while stirring, and continue steam heating to 100°C; Urea-formaldehyde reaction: add 107kg 38wt% formaldehyde solution into the reactor, and stop steam heating at the same time. After the addition of formaldehyde solution, the temperature in the reactor is 110°C, and the reaction is continued with stirring for 20 minutes to obtain urea-formaldehyde; Post-treatment: After the urea formaldehyde is cooled to 25°C, a modified adsorbent is added to the urea formaldehyde and mixed evenly. The amount of the modified adsorbent added to the urea formaldehyde product is 0.3 g / L to obtain a urea formaldehyde product. The modified adsorbent is the chitosan-nanocrystalline cellulose composite aerogel obtained in Preparation Example 4.
[0042] Example 3 The difference between Example 3 and Example 1 is that in Example 3, the amount of the modified adsorbent added to the urea formaldehyde finished product is 0.1 g / L.
[0043] Example 4 The difference between Example 4 and Example 1 is that in Example 4, the amount of the modified adsorbent added to the urea formaldehyde product is 0.5 g / L.
[0044] Example 5 The difference between Example 5 and Example 1 is that in Example 5, the modified adsorbent is the chitosan-nanocrystalline cellulose composite aerogel prepared in Preparation Example 5.
[0045] Example 6 The difference between Example 6 and Example 1 is that in Example 6, the modified adsorbent is the chitosan-nanocrystalline cellulose composite aerogel prepared in Preparation Example 6.
[0046] Example 7 The difference between Example 7 and Example 1 is that in Example 7, the modified adsorbent is the chitosan-nanocrystalline cellulose composite aerogel prepared in Preparation Example 7.
[0047] Example 8 The difference between Example 8 and Example 1 is that in Example 8, the modified adsorbent is the chitosan-nanocrystalline cellulose composite aerogel prepared in Preparation Example 8.
[0048] Example 9 The difference between Example 9 and Example 1 is that in Example 9, the modified adsorbent is the chitosan-nanocrystalline cellulose composite aerogel prepared in Preparation Example 9.
[0049] Example 10 The difference between Example 10 and Example 1 is that in Example 10, the modified adsorbent is the chitosan-nanocrystalline cellulose composite aerogel prepared in Preparation Example 10.
[0050] Embodiment 11 The difference between Example 11 and Example 1 is that in Example 11, the modified adsorbent is the chitosan-nanocrystalline cellulose composite aerogel prepared in Preparation Example 11.
[0051] Example 12 The difference between Example 12 and Example 1 is that in Example 12, the modified adsorbent is the chitosan-nanocrystalline cellulose composite aerogel prepared in Preparation Example 12.
[0052] Example 13 The difference between Example 13 and Example 1 is that in Example 13, the amount of water added to the reactor is 430 kg, and the mass ratio of water, urea and formaldehyde solution is 0.43:2.56:0.95.
[0053] Embodiment 14 The difference between Example 14 and Example 1 is that in Example 14, the amount of water added to the reactor is 430 kg, and the mass ratio of water, urea and formaldehyde solution is 0.43:4.45:1.26. Comparative Example
[0054] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, urea formaldehyde is not post-treated. Test methods
[0055] 1. Urea formaldehyde finished products were prepared according to the processes of Examples 1-14 and Comparative Example 1, and free formaldehyde was detected on the urea formaldehyde finished products. The results are recorded in Table 1. The changes in formaldehyde in the environment after the urea formaldehyde finished products were applied as liquid fertilizers were detected according to the following test method: 45 potted money trees with similar growth conditions were selected and divided into a group of three pots. The same urea formaldehyde finished product was applied to the potted plants in the same group. The application rate of the urea formaldehyde finished product was 250 mL / pot. The potted plants were covered with sealed containers of the same size and good heat dissipation, and the sealed containers and potted plants were placed in an open field to receive natural light. The experimental time was 8 days. The formaldehyde content in the sealed containers was detected on the 8th day. The results of the same group were averaged and the results were recorded in Table 1.
[0056] Table 1 Free formaldehyde content of urea formaldehyde finished products and after application project Free formaldehyde / (%) Formaldehyde in container / (mg) Example 1 0.0238 1.68 Example 2 0.0225 1.64 Example 3 0.0295 2.01 Example 4 0.0312 1.98 Example 5 0.0286 1.95 Example 6 0.0279 2.08 Example 7 0.0195 1.29 Example 8 0.0201 1.34 Example 9 0.0130 0.91 Example 10 0.0127 0.93 Embodiment 11 0.0165 1.21 Example 12 0.0172 1.26 Example 13 0.1062 3.01 Embodiment 14 0.0981 2.95 Comparative Example 1 0.1863 3.95 According to Table 1, Examples 1-2 and Comparative Example 1, it can be seen that the urea formaldehyde finished product prepared in Comparative Example 1 has a lower content of free formaldehyde, and after application, the formaldehyde content in the application environment is lower. Compared with Comparative Example 1, the urea formaldehyde finished product of Examples 1-2 has a lower content of free formaldehyde, and the content of free formaldehyde in the use environment is even lower. In Examples 1-2, urea formaldehyde is post-treated and a modified adsorbent is added to the urea formaldehyde, indicating that the modified adsorbent can effectively reduce the free formaldehyde in the urea formaldehyde finished product and the environment after application.
[0057] The modified adsorbent is chitosan-nanocrystalline cellulose composite aerogel. Both chitosan and nanocrystalline cellulose have large specific surface areas and can fix free formaldehyde by physical adsorption. At the same time, both chitosan and nanocrystalline cellulose contain more active groups. Chitosan contains more amino groups, while nanocrystalline cellulose contains more amino groups and hydroxyl groups. Amino groups can undergo nucleophilic addition reaction with formaldehyde molecules to form C=N, and free formaldehyde can be fixed by chemical adsorption. Hydroxyl groups can form stable covalent bonds with formaldehyde. Therefore, chitosan-nanocrystalline cellulose composite aerogel can adsorb and fix formaldehyde by physical-chemical adsorption, thereby reducing free formaldehyde in urea formaldehyde finished products. At the same time, after the urea formaldehyde finished products are applied, urea formaldehyde is slowly decomposed, and the generated formaldehyde can also be adsorbed and fixed by the modified adsorbent, thereby reducing the formaldehyde content in the application environment and reducing the adverse effects of urea formaldehyde on the environment after application.
[0058] Compared with Example 1, the formaldehyde content in the urea formaldehyde product prepared in Example 3-4 and in the environment after application is increased. The amount of modified adsorbent added in Example 3-4 is adjusted, which shows that the amount of modified adsorbent added affects the performance of the urea formaldehyde product and after application. Too much or too little addition of adsorption modifier is likely to affect the use effect of the modified adsorbent. When the amount of modified adsorbent added is too little, the adsorption and fixation speed of the modified adsorbent is significantly different from the generation and release speed of formaldehyde, so that more formaldehyde volatilizes and diffuses, thereby increasing the free formaldehyde content. When the amount of modified adsorbent added is too much, the modified adsorbent is easily unevenly distributed in the urea formaldehyde, thereby affecting the adsorption effect of the modified adsorbent.
[0059] Compared with Example 1, the formaldehyde content in the urea formaldehyde finished product prepared in Example 5-6 and the environment after application is increased. During the preparation of the modified adsorbent used in Example 5-6, the amount of chitosan added was changed, indicating that the amount of chitosan added has an effect on the formaldehyde adsorption performance of the modified adsorbent. The appropriately added chitosan can be uniformly dispersed in the mixed solution together with the nanocrystalline cellulose. The chitosan can form a new network structure with the nanocrystalline cellulose, so that the chitosan-nanocrystalline cellulose composite aerogel has a more complex network structure, thereby improving the adsorption performance of the chitosan-nanocrystalline cellulose composite aerogel.
[0060] Compared with Example 1, the formaldehyde content of the urea formaldehyde finished product prepared in Example 7-8 and the environment after application is reduced. When preparing the modified adsorbent used in Example 7-8, the chitosan-nanocrystalline cellulose composite aerogel was post-treated, indicating that the post-treatment of the chitosan-nanocrystalline cellulose composite aerogel by ammoniation treatment can improve the adsorption performance of the modified adsorbent. The ammoniation treatment can make the chitosan-nanocrystalline cellulose composite aerogel contain more amino groups, and the amino groups are easily combined with the aldehyde groups of formaldehyde, thereby improving the adsorption and fixation performance of the chitosan-nanocrystalline cellulose composite aerogel for formaldehyde.
[0061] Compared with Example 7, the formaldehyde content in the urea formaldehyde finished product prepared in Example 9-10 and the environment after application is reduced. In Example 9-10, sodium alginate gel powder embedded with formaldehyde-degrading bacteria is added to the modified adsorbent, indicating that the sodium alginate gel powder embedded with formaldehyde-degrading bacteria has a better effect on reducing the free formaldehyde content. The sodium alginate gel powder embeds the formaldehyde-degrading bacteria, which can reduce the adverse effects of the external environment on the formaldehyde-degrading bacteria, thereby improving the survival rate of the formaldehyde-degrading bacteria. Sodium alginate gel powder embedded with formaldehyde-degrading bacteria is dispersed in a suspension of a modified adsorbent. The modified adsorbent can adsorb and combine with the sodium alginate gel powder, so that the formaldehyde-degrading bacteria are fixed on the surface of the modified adsorbent along with the sodium alginate gel powder. The modified adsorbent absorbs and fixes formaldehyde to achieve formaldehyde enrichment, which is convenient for the formaldehyde-degrading bacteria to decompose the formaldehyde in a concentrated manner. The formaldehyde-degrading bacteria that are not combined with the modified adsorbent can be dispersed in the urea formaldehyde and degrade the formaldehyde that is not fixed by the modified adsorbent.
[0062] Compared with Example 9, the formaldehyde content in the urea formaldehyde finished product prepared in Example 11-12 and the environment after application is increased. In Example 11-12, the mass ratio of chitosan-nanocrystalline cellulose composite aerogel and sodium alginate gel powder embedded with formaldehyde-degrading bacteria was changed, indicating that the addition amount of sodium alginate gel powder embedded with formaldehyde-degrading bacteria has an effect on the free formaldehyde content. When the addition amount is too small, the content of formaldehyde-degrading bacteria is small, the decomposition rate of formaldehyde decreases, and the free formaldehyde content increases. When the addition amount is too large, the sodium alginate gel powder is unevenly distributed, which affects the degradation effect of formaldehyde-degrading bacteria.
[0063] Compared with Example 1, the formaldehyde content in the urea formaldehyde finished product prepared in Example 13-14 and the environment after application is increased. The mass ratio of water, urea and formaldehyde solution was adjusted in Example 13-14, indicating that the mass ratio of water, urea and formaldehyde solution has an effect on the free formaldehyde content. The amount of water added affects the concentration of urea and formaldehyde in the reactor, thereby affecting the reaction rate and distribution uniformity of formaldehyde and urea. The mass ratio of urea to formaldehyde directly affects the content of free formaldehyde in the urea formaldehyde product, as well as the composition and degree of polymerization of the urea formaldehyde product, thereby affecting the formaldehyde content in the closed container.
[0064] 2. Add a blank group, which contains three pots of money tree plants with similar growth conditions. No fertilizer is applied to the blank group potted plants. The test conditions of the blank group are the same as those of Examples 1-14 and Comparative Example 1. All of them are covered with closed containers and placed in an open field to receive natural light. The experimental time is 8 days. On the 8th day, the nitrogen utilization rate and sustained fertilizer effect of Examples 1-2, Examples 9-10, Examples 13-14, and Comparative Example 1 are tested, and the results are recorded in Table 2.
[0065] After the nitrogen utilization rate and the continuous fertilizer effect were recorded, the sealed container was removed, and the potted plants of Examples 1-2, Examples 9-10, Examples 13-14, Comparative Example 1 and the blank group were placed in an open field and cultivated in a normal cultivation manner. After two months, the growth height of the potted plants was recorded, that is, the difference between the potted plant height two months later and the potted plant height at the beginning of the test. The results of the potted plants in the same group were averaged and the results were recorded in Table 1.
[0066] Table 2 Effect of urea formaldehyde application project Nitrogen utilization rate / % Sustained fertilizer effect / day Growth height / cm Example 1 58 144 16.28 Example 2 59 146 16.31 Example 9 68 143 18.13 Example 10 67 145 18.01 Example 13 50 131 15.20 Embodiment 14 52 132 15.34 Comparative Example 1 46 124 13.26 Blank Group —— —— 8.26 According to Table 2, Examples 1-2 and the blank group, it can be seen that the urea formaldehyde prepared in Example 1-2 is used as a fertilizer, which can effectively increase the growth height of the plants and is beneficial to the growth of the plants. The blank group did not fertilize the potted plants, while urea formaldehyde was applied to the potted plants in Example 1-2, indicating that urea formaldehyde, as a nitrogen fertilizer, has a promoting effect on plant growth. Urea formaldehyde can slowly decompose to generate urea, which provides nitrogen elements for plant growth, making the plants of Example 1-2 grow taller.
[0067] Compared with Example 1, the nitrogen utilization rate, sustained fertilizer effect and plant growth height of Example 13-14 are inferior to those of Example 1. The mass ratio of water, urea and formaldehyde solution was adjusted in Example 13-14, indicating that the mass ratio of water, urea and formaldehyde solution has some influence on the effect of urea formaldehyde as a nitrogen fertilizer. The mass ratio of the three is likely to affect the polymerization and composition of the urea formaldehyde product, and then affect the decomposition rate of the urea formaldehyde product, thereby affecting the plant's absorption and utilization of nitrogen, making the growth of the plant applied with Example 13-14 worse than that of Example 1.
[0068] Compared with Example 1, the nitrogen utilization rate and plant growth height of Comparative Example 1 are inferior to those of Example 1. In Comparative Example 1, no modified adsorbent is added to urea formaldehyde, which indicates that the addition of the modified adsorbent has a beneficial effect on the growth of the plants. After the application of urea formaldehyde, it can be seen from Table 1 that the urea formaldehyde finished product prepared in Comparative Example 1 contains a high level of free formaldehyde, and the formaldehyde content in the sealed container after the test is high, indicating that the failure to add the modified adsorbent easily increases the formaldehyde content after the application of urea formaldehyde, and the increase in formaldehyde content has an adverse effect on the growth state of the applied plants, which is manifested in the reduction of the nitrogen utilization rate of the plants, the decrease in the growth height of the plants, and the like.
[0069] Compared with Example 1, the nitrogen utilization rate and plant growth height of Example 9-10 are better than those of Example 1. In Example 9-10, sodium alginate gel powder embedded with formaldehyde-degrading bacteria is added to the modified adsorbent, indicating that the sodium alginate gel powder embedded with formaldehyde-degrading bacteria has an effect on the growth of plants. The sodium alginate gel powder embedded with formaldehyde-degrading bacteria enters the soil with the application of urea formaldehyde. The sodium alginate gel powder has a protective effect on the formaldehyde-degrading bacteria and can increase the survival rate of the formaldehyde-degrading bacteria. At the same time, the sodium alginate gel powder can be degraded to reduce the impact on the environment. At the same time, the formaldehyde-degrading bacteria can carry out natural activities to degrade formaldehyde in the environment. The products are carbon dioxide and water, which can be used for plant growth and development.
[0070] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A urea formaldehyde production process, characterized in that: The following steps are involved: Preheating: After the reactor is heated to 45-55°C, hot water at 45-55°C is introduced; Dissolution: Continue steam heating, raise the temperature of the reactor to 70-80°C, add urea while stirring, and continue steam heating to 90-100°C; Urea-formaldehyde reaction: add 35-38 wt% formaldehyde solution into the reactor, stop steam heating, and continue stirring and reacting for 15-20 minutes to obtain urea-formaldehyde; Post-treatment: After the urea formaldehyde is cooled to 20-25°C, the modified adsorbent is added to the urea formaldehyde and mixed evenly to obtain the urea formaldehyde product.
2. A urea formaldehyde production process according to claim 1, characterized in that: The mass ratio of the water, urea and formaldehyde solution is (0.43-0.45):(3.98-4.01):(1.01-1.07).
3. A urea formaldehyde production process according to claim 1, characterized in that: The modified adsorbent is added in an amount of 0.2-0.3 g / L in the urea formaldehyde finished product.
4. A urea formaldehyde production process according to claim 1, characterized in that: The modified adsorbent is chitosan-nanocrystalline cellulose composite aerogel.
5. A urea formaldehyde production process according to claim 4, characterized in that: The preparation method of the chitosan-nanocrystalline cellulose composite aerogel comprises the following steps: dispersing nanocrystalline cellulose in a 2-3wt% acetic acid solution, adding chitosan, stirring until completely dissolved to obtain a mixed solution, adding potassium persulfate, reacting for 10-12 minutes, adding acrylic acid solution and sodium hydroxide solution, then adding acrylamide, ultrasonicating until uniform dispersion, adding N,N'-methylenebisacrylamide solution, reacting for 30-40 minutes, continuing to react at 60°C for 6 hours, dialyzing for 7 days, and freeze-drying to obtain the chitosan-nanocrystalline cellulose composite aerogel.
6. A urea formaldehyde production process according to claim 5, characterized in that: The chitosan-nanocrystalline cellulose composite aerogel is further subjected to the following post-treatment: epichlorohydrin, perchloric acid solution and anhydrous ethanol are mixed to obtain a mixed solution, the chitosan-nanocrystalline cellulose composite aerogel is placed in the mixed solution, left to stand for 12 hours, washed with anhydrous ethanol, heated in a water bath at 50° C., a mixed solution of ethylenediamine and anhydrous ethanol is added, left to stand for 12 hours, and freeze-dried.
7. A urea formaldehyde production process according to claim 6, characterized in that: In the post-treatment, before adding the modified adsorbent, the following treatment is performed: the modified adsorbent is ultrasonically dispersed in water, sodium alginate gel powder with formaldehyde-degrading bacteria embedded therein is added, ultrasonically treated for 20-25 minutes, allowed to stand for 30-35 minutes, and freeze-dried.
8. A urea formaldehyde production process according to claim 7, characterized in that: The mass ratio of the chitosan-nanocrystalline cellulose composite aerogel to the sodium alginate gel powder embedded with formaldehyde-degrading bacteria is 1:(0.08-0.12).
9. A urea formaldehyde production process according to claim 7, characterized in that: The preparation method of the sodium alginate gel powder embedded with formaldehyde-degrading bacteria is as follows: formaldehyde-degrading bacteria are dispersed in physiological saline to obtain a bacterial suspension, the bacterial suspension is mixed with a sodium alginate solution and stirred evenly, a 4wt% calcium chloride solution is dropped into the solution, and after solidification for 2-2.5h to form, the sodium alginate microspheres are placed in physiological saline, solidified at 4-6°C for 12-13h, centrifuged and dried to obtain the sodium alginate gel powder embedded with formaldehyde-degrading bacteria.
Citation Information
Patent Citations
Modified chitosan / nanocellulose composite aerogel and preparation method and application thereof
CN106243282A
Preparation method of composite catalytic system capable of efficiently degrading phenol-containing wastewater
CN109879449A
Acrylic copolymer magnetic porous hydrogel adsorbent and preparation method thereof
CN112029117A
Integrated preparation process and application of urea-aldehyde multi-nutrient element biodegradable polymer slow / controlled release liquid fertilizer and solid granular fertilizer
CN118496019A